Comparative floral micromorphology and anatomy of species of Bulbophyllum section Napelli (Orchidaceae), a Neotropical section widely distributed in forest habitats - Nunes, Elaine Lopes Pereira [UNESP]; Smidt, Eric de Camargo; Stuetzel, Thomas; Coan, Alessandra Ike [UNESP] (Wiley-Blackwell, 2015)
Bulbophyllum section Napelli, as recently circumscribed based on molecular analyses, comprises 12 species. These occur as epiphytes in the Brazilian Atlantic Rain Forest and in gallery forests in the cerrado vegetation, and thus differ from other Neotropical sections of Bulbophyllum, which are more variable in habit and habitat. To identify diagnostic characteristics that are representative of this section and to confirm whether there are characteristics that are related to their habit and habitat, their floral micromorphology and anatomy were studied using conventional techniques. Bulbophyllum section Napelli is characterized by sepals with sunken glandular trichomes and stomata on the abaxial surface, reduced petals with one vascular bundle (sometimes lacking), an entire labellum with a secretory sulcus on the adaxial surface and a keel with stomata or glandular trichomes on the abaxial surface, two pollinia, and crystalliferous idioblasts in all floral parts. Our data enable us to distinguish between species and show congruence with the present circumscription of B. section Napelli. The labellar epidermal surface of three closely-related species was unusual in its possession of unicellular trichomes and these appear to function as osmophores. A relationship between striate surfaces, iridescence and pollinator attraction related to the epiphytic habit and forest habitat is proposed.
Keywords: Bulbophyllum atropurpureum; Bulbophyllum campos-portoi; Bulbophyllum granulosum; Bulbophyllum malachadenia; Bulbophyllum regnellii; Cell wall striation; Nectary; Petal reduction osmophore; Secretory epidermis